Energy, economy, financial development, and ecological footprint in Singapore - Raihan, Asif (Energy Economics Letters, 2024)
The escalating energy consumption resulting from rapid economic expansion is causing a decline in ecological health, therefore exacerbating the issue of climate change on a global scale. The juxtaposition of Singapore’s ranking as having the most robust financial market with the largest ecological deficit globally implies the potential validity of the trade-off theory. The purpose of this study is to analyze the influence of Singapore’s financial growth, energy use and economic development on the nation’s ecological footprint. The investigation applied the Auto Regressive Distributed Lag (ARDL) method by using the annual time series data spanning from 1979 to 2021. The stationarity of data was confirmed by using several unit root tests. The ARDL bounds test revealed evidence for long term cointegration among the variables. The empirical results exposed that a 1% upsurge in financial growth, energy use, and economic expansion leads to a corresponding long-term increase in ecological footprint of 0.77%, 1.11% and 0.32%, as well as short-term increases of 0.44%, 0.61%, and 0.13%, respectively. Several diagnostic tests were used to confirm the accuracy of the ARDL outcomes. The findings of the analysis hold significant relevance for policymakers as they can inform the development of prudent policies that promote sustained economic prosperity without compromising environmental integrity.